Hasn't Child Abuse Been Overlooked? An Evaluation of Abused Children Who Visited the Emergency Department with Sentinel Injuries - Han Bit Kim; Hyun Noh (MDPI AG, 2024)
Objective: Effective child abuse intervention requires understanding its prevalence. While obtaining a comprehensive national estimate of child abuse cases is challenging, sentinel injuries-minor yet unusual injuries like bruises or wounds in pre-cruising-age children-can provide an indicative measure. Using the National Emergency Department Information System (NEDIS) data, this study aimed to gauge the prevalence of sentinel injuries using diagnostic codes in children under 12 months who visited emergency centers in South Korea and to evaluate the extent of child abuse screening in these cases. Methods: This cross-sectional study used diagnostic codes indicative of sentinel injuries previously defined using the Delphi method. This study, using NEDIS data, included children under 12 months who visited emergency centers nationwide from 2014 to 2021 for reasons of injury. Children injured in car accidents were excluded. Independent variables included patient demographics, the injury mechanism, intentionality, the route of arrival, the emergency center level, the triage level, and specialist consultation. Dependent variables were the presence of a sentinel injury code, and whether diagnostic tests for child abuse were conducted. Results: Based on NEDIS and national statistical data, the frequency from 2014 to 2021 averaged 2501 per 100,000 of the population. Of the 186,065 patients studied, 63,131 (33.9%) had a diagnostic code corresponding to a sentinel injury. The proportion of patients undergoing diagnostic tests for suspected child abuse was 36.9% for those with sentinel injuries and 43.8% for those with other codes. The percentage of children with sentinel injuries receiving diagnostic tests increased annually, from 32.4% in 2014 to 54.4% in 2021. By institution, the rates were 36.4% for regional emergency centers, 38.4% for local emergency centers, and 20.0% for local emergency institutions. Conclusions: A significant proportion of children presenting to emergency departments had sentinel injury codes. However, the rate of diagnostic tests conducted for suspected child abuse in these cases remains suboptimal. Although there has been an upward trend in testing rates in recent years, there is a pressing need for increased attention to and enhancement in screening for child abuse among children with sentinel injury codes.